Boosted Electrocatalytic N2 Reduction to NH3 by Defect‐Rich MoS2 Nanoflower. Issue 30 (19th September 2018) - Li, Xianghong; Li, Tingshuai; Ma, Yongjun; Wei, Qin; Qiu, Weibin; Guo, Haoran; Shi, Xifeng; Zhang, Peng; Asiri, Abdullah M.; Chen, Liang; Tang, Bo; Sun, Xuping
Abstract: The industrial artificial fixation of atmospheric N2 to NH3 is carried out using the Haber–Bosch process that is not only energy‐intensive but emits large amounts of greenhouse gas. Electrochemical reduction offers an environmentally benign and sustainable alternative for NH3 synthesis. Although Mo‐dependent nitrogenases and molecular complexes effectively catalyze the N2 fixation at ambient conditions, the development of a Mo‐based nanocatalyst for highly performance electrochemical N2 fixation still remains a key challenge. Here, greatly boosted electrocatalytic N2 reduction to NH3 with excellent selectivity by defect‐rich MoS2 nanoflowers is reported. In 0.1m Na2 SO4, this catalyst attains a high Faradic efficiency of 8.34% and a high NH3 yield of 29.28 µg h −1 mg −1 cat. at − 0.40 V versus reversible hydrogen electrode, much larger than those of defect‐free counterpart (2.18% and 13.41 µg h −1 mg −1 cat. ), with strong electrochemical stability. Density functional theory calculations show that the potential determining step has a lower energy barrier (0.60 eV) for defect‐rich catalyst than that of defect‐free one (0.68 eV). Abstract : Defect‐rich MoS2 nanoflower acts as a superb elelctrocatalyst for N2 reduction reaction, it attains a high Faradic efficiency of 8.34% and a high NH3 yield of 29.28 µg h −1 mg −1 cat., with strong electrochemical stability. Density functional theory calculations show that the proton‐electron coupling transferring process (*NH2 →*NH3 ) as the potential determining step has a lower energy barrier (0.60 eV).